Heterocyclic spice controlled and slow release type MOFs (Metal-Organic Frameworks) material as well as preparation method and application thereof
By preparing MOFs materials with specific structures, the problems of volatile and unstable fragrances are solved, and the efficient adsorption and controlled and sustained release of fragrances are achieved. It is suitable for fragrance replenishment of daily chemicals, tobacco and other products.
Patent Information
- Application Number
- CN202411697312.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
AI Technical Summary
The fragrances are volatile and unstable, limiting their use in industrial applications.
By preparing heterocyclic fragrance controlled sustained-release MOFs materials with specific pore environment, pore size and pore volume, the adsorption and controlled sustained-release of fragrance are achieved using its high specific surface area and rich micropore structure.
This material significantly improves the adsorption amount and sustained release effect of the fragrance, ensuring that the fragrance is slowly released at room temperature and is slow to release under high temperature conditions, extending the retention time of the fragrance.
Smart Images

Figure CN119529303A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of spices and flavors, and in particular to a heterocyclic spice controlled slow-release MOFs material and a preparation method and application thereof. Background Art
[0002] Flavors and fragrances are a class of substances with aroma or fragrance. Direct fragrance addition can give products flavor, improve product odor, and play antibacterial and antioxidant roles in products. They have been widely used in food, daily chemicals, tobacco and other fields. However, most flavors and fragrances are liquid aromatic compounds with low boiling points and high volatility, especially nitrogen-containing and oxygen-containing heterocyclic spices, which are very unstable under environmental conditions such as light, air and high temperature, which to a certain extent limits their industrial application. Controlled-release technology has become an important research area in the flavor and fragrance industry. Researching new flavor sustained-release agents to solve the problem of volatility and instability of flavors and fragrances has important practical value. Summary of the invention
[0003] The purpose of the present invention is to provide a heterocyclic fragrance controlled-release MOFs material and a preparation method and application thereof. The prepared MOFs material with a specific pore environment, pore size and pore volume has excellent adsorption and controlled-release properties for heterocyclic fragrances, and can solve the problem of volatility and instability of fragrances and flavors.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing a heterocyclic fragrance controlled sustained-release MOFs material, comprising the following steps:
[0006] Mixing soluble cobalt salt, 2-methylimidazole and solvent, and performing crystallization to obtain heterocyclic fragrance controlled slow-release MOFs material;
[0007] The solvent is methanol or water;
[0008] When the solvent is methanol: the usage ratio of the soluble cobalt salt, 2-methylimidazole and solvent is 2.0-3.0 g: 6.0-7.0 g: 400 mL; or, the usage ratio of the soluble cobalt salt, 2-methylimidazole and solvent is 3.0-4.0 g: 3.0-4.0 g: 200 mL; the crystallization temperature is 15-30° C.;
[0009] When the solvent is water, the usage ratio of the soluble cobalt salt, 2-methylimidazole and water is 0.3-1.0 g:5.0-6.0 g:80-100 mL; and the crystallization temperature is 50-80° C.
[0010] Preferably, the soluble cobalt salt is cobalt nitrate, cobalt chloride, cobalt acetate or cobalt sulfate.
[0011] Preferably, the soluble cobalt salt, 2-methylimidazole and solvent are mixed for 1 to 10 minutes.
[0012] Preferably, the crystallization time is 12 to 24 hours.
[0013] The present invention provides a heterocyclic fragrance controlled sustained-release MOFs material prepared by the preparation method described in the above technical solution.
[0014] The present invention provides the use of the heterocyclic fragrance controlled-release MOFs material described in the above technical solution as an adsorbent in the adsorption and controlled-release of fragrances and flavors.
[0015] Preferably, the application method comprises the following steps:
[0016] The heterocyclic fragrance controlled-release MOFs material and the heterocyclic fragrance are placed in the same closed environment for adsorption.
[0017] Preferably, the heterocyclic fragrance includes one of 3-acetylpyridine, 2-acetylpyridine, 2-acetylpyrrole and 2,3,5-trimethylpyrazine.
[0018] Preferably, the usage ratio of the heterocyclic fragrance controlled-release MOFs material to the heterocyclic fragrance is 30-60 mg:100-300 μL.
[0019] Preferably, the adsorption temperature is 50-100° C., and the adsorption time is 5-10 h.
[0020] The present invention provides a method for preparing a heterocyclic fragrance controlled slow-release MOFs material, and a MOFs material with a specific pore environment, pore size and pore volume is prepared by adjusting the raw material ratio, and the prepared MOFs material has a high specific surface area, which can provide a large number of adsorption sites for fragrance molecules. The micropore size of MOFs can ensure that the fragrance molecules enter the internal pores and prevent them from escaping too quickly, thereby achieving a slow-release effect; at the same time, the pore structure of MOFs is usually very orderly, which helps the transmission and distribution of fragrance molecules in the pores, promotes the uniform adsorption and release of fragrance molecules, and improves the slow-release effect. Therefore, the MOFs materials prepared by the present invention have a high fragrance adsorption amount and can be slowly released at room temperature. Among them, 300nm ZIF-67 has a large specific surface area and rich microporous structure, showing the best adsorption effect (1083mg / g), and still has a retention rate of 62.2% after being placed at room temperature for 20 days, and only releases 6.3% within 60 minutes under high temperature conditions of 80°C. The MOFs material prepared by the invention has excellent adsorption and sustained-release effects on the representative heterocyclic fragrance 3-acetylpyridine.
[0021] The controlled-release MOFs material of the present invention has a simple preparation process, has a rich microporous structure, an adjustable pore size, a large specific surface area and a diverse topological structure, can achieve the controlled-release of spices, is an effective method for efficient adsorption and controlled-release materials, provides favorable guidance for the development and utilization of heterocyclic spices, and has a relatively broad application prospect.
[0022] The controlled-release MOFs material of the present invention can effectively adsorb heterocyclic fragrances and control their release, and can provide flavoring support for daily chemicals, tobacco and other products. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 XRD diagram of MOFs materials in Examples 1 to 3;
[0024] Figure 2 It is the SEM image of the MOFs material in Examples 1 to 3;
[0025] Figure 3 BET test results of MOFs materials in Examples 1 to 3, N2 adsorption-desorption isotherms (a) and pore size distribution curves (b);
[0026] Figure 4 The adsorption performance of the MOFs materials in Examples 1 to 3 on 3-acetylpyridine;
[0027] Figure 5 is the retention rate of 3-acetylpyridine after the MOFs material in Examples 1 to 3 is placed at room temperature for 20 days after adsorption of 3-acetylpyridine;
[0028] Figure 6 The fragrance release curves of the MOFs materials in Examples 1 to 3 at 80° C. change with time. DETAILED DESCRIPTION
[0029] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0030] The present invention provides a method for preparing a heterocyclic fragrance controlled sustained-release MOFs material, comprising the following steps:
[0031] Mixing soluble cobalt salt, 2-methylimidazole and solvent, and performing crystallization to obtain heterocyclic fragrance controlled slow-release MOFs material;
[0032] The solvent is methanol or water;
[0033] When the solvent is methanol: the usage ratio of the soluble cobalt salt, 2-methylimidazole and solvent is 2.0-3.0 g: 6.0-7.0 g: 400 mL; or, the usage ratio of the soluble cobalt salt, 2-methylimidazole and solvent is 3.0-4.0 g: 3.0-4.0 g: 200 mL; the crystallization temperature is 15-30° C.;
[0034] When the solvent is water, the usage ratio of the soluble cobalt salt, 2-methylimidazole and water is 0.3-1.0 g:5.0-6.0 g:80-100 mL; and the crystallization temperature is 50-80° C.
[0035] In the present invention, the soluble cobalt salt is preferably cobalt nitrate, cobalt chloride, cobalt acetate or cobalt sulfate.
[0036] In the present invention, the solvent is methanol or water.
[0037] In the present invention, the mixing time of the soluble cobalt salt, 2-methylimidazole and the solvent is preferably 1 to 10 minutes, more preferably 5 to 10 minutes.
[0038] When the solvent is methanol: the present invention preferably adds a soluble cobalt salt to methanol under room temperature and magnetically stirs to obtain a cobalt salt solution, adds 2-methylimidazole to methanol and magnetically stirs to obtain a 2-methylimidazole solution, mixes the cobalt salt solution and the 2-methylimidazole solution, crystallizes them, and successively centrifuges, washes with ethanol and dries the resulting product to obtain a heterocyclic fragrance controlled sustained-release MOFs material.
[0039] When the solvent is methanol: the crystallization temperature is 15-30°C, more preferably 20-25°C, and the crystallization time is preferably 12-24h; the crystallization is preferably carried out under static, stirring or ultrasonic conditions; the present invention has no special limitation on the stirring or ultrasound, and it can be carried out according to the stirring or ultrasound known in the art.
[0040] In the present invention, when the solvent is methanol, the usage ratio of the soluble cobalt salt, 2-methylimidazole and the solvent is 2.0-3.0 g:6.0-7.0 g:400 mL, preferably 2.933 g:6.489 g:400 mL.
[0041] As another embodiment of the present invention, when the solvent is methanol, the usage ratio of the soluble cobalt salt, 2-methylimidazole and the solvent is 3.0-4.0 g:3.0-4.0 g:200 mL, preferably 3.493 g:3.941 g:200 mL.
[0042] In the present invention, when the solvent is water: the present invention preferably adds a soluble cobalt salt to water under crystallization temperature conditions and magnetically stirs to obtain a cobalt salt solution, and simultaneously adds 2-methylimidazole to water and magnetically stirs to obtain a 2-methylimidazole solution. After the cobalt salt solution and the 2-methylimidazole solution are mixed, crystallized, filtered, washed with water, and dried, a heterocyclic fragrance controlled sustained-release MOFs material is obtained.
[0043] In the present invention, when the solvent is water: the usage ratio of the soluble cobalt salt, 2-methylimidazole and water is 0.3-1.0g:5.0-6.0g:80-100mL, more preferably 0.45g:5.5g:92mL; the crystallization temperature is 50-80°C, more preferably 60°C (oil bath); the crystallization time is preferably 12-24h, more preferably 15-20h; the crystallization is preferably carried out under static or stirring conditions.
[0044] The present invention provides a heterocyclic fragrance controlled sustained-release MOFs material prepared by the preparation method described in the above technical solution.
[0045] The present invention provides the use of the heterocyclic fragrance controlled-release MOFs material described in the above technical solution as an adsorbent in the adsorption and controlled-release of fragrances and flavors.
[0046] In the present invention, the method of application preferably comprises the following steps:
[0047] The heterocyclic fragrance controlled-release MOFs material and the heterocyclic fragrance are placed in the same closed environment for adsorption.
[0048] In the present invention, the heterocyclic fragrance preferably includes one of 3-acetylpyridine, 2-acetylpyridine, 2-acetylpyrrole and 2,3,5-trimethylpyrazine.
[0049] The present invention preferably places the heterocyclic fragrance controlled-release MOFs material and the heterocyclic fragrance in the same closed container, and places the container in an oven for adsorption.
[0050] In the present invention, the usage ratio of the heterocyclic fragrance controlled-release MOFs material to the heterocyclic fragrance is preferably 30-60 mg:100-300 μL, more preferably 40-50 mg:200 μL, and further preferably 50 mg:200 μL.
[0051] In the present invention, the adsorption temperature is preferably 50 to 100° C., more preferably 60 to 80° C., and the adsorption time is preferably 5 to 10 h, more preferably 6 to 8 h.
[0052] In the present invention, the method for testing the adsorption performance of fragrance is preferably: taking the material after adsorption, extracting the essence in the material with an extraction solvent, and testing it with GC-MS; the extraction solvent is preferably ethanol, acetone or acetonitrile, the amount ratio of the extraction solvent to the material after adsorption is preferably 1-5mL:3-6mg, more preferably 2mL:5mg, the extraction temperature is preferably 30-50°C, more preferably 40°C, the extraction time is preferably 20-60min, more preferably 30min; the extraction is preferably carried out under ultrasonic or stirring conditions. After the extraction is completed, the obtained product is centrifuged, the supernatant is filtered, and tested with GC-MS.
[0053] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0054] Example 1
[0055] Take 2.933g Co(NO3)2·6H2O and dissolve it in 200mL methanol at room temperature to obtain solution A, take 6.489g 2-methylimidazole and dissolve it in 200mL methanol at room temperature to obtain solution B, add solution B to solution A and stir for 10min, let stand at 25℃ for 24h, centrifuge, wash with ethanol, and dry in an oven at 60℃ overnight. The obtained material is recorded as ZIF-67-300.
[0056] Example 2
[0057] 3.493 g of Co(NO3)2·6H2O was dissolved in 100 mL of methanol at room temperature to obtain solution A. 3.941 g of 2-methylimidazole was dissolved in 100 mL of methanol at room temperature to obtain solution B. Solution B was added to solution A and stirred for 10 min. The mixture was allowed to stand at 25°C for 24 h, centrifuged, washed with ethanol, and dried in an oven at 60°C overnight. The obtained material was recorded as ZIF-67-700.
[0058] Example 3
[0059] Take 0.45g Co(NO3)2·6H2O and dissolve it in 12mL deionized water under 60℃ oil bath condition to obtain solution A, take 5.50g 2-methylimidazole and dissolve it in 80mL deionized water under 60℃ oil bath condition to obtain solution B, add solution B to solution A, stir for 10min under 60℃ oil bath condition, let stand for 20h, filter, wash with water, and dry in 60℃ oven overnight. The obtained material is recorded as ZIF-67-1700.
[0060] Characterization and performance testing
[0061] 1) Figure 1 The X-ray powder diffraction (XRD) diagrams of the materials obtained in Examples 1 to 3 are shown in FIG. Figure 1 It can be seen that under different raw material ratios, the three materials all showed XRD diffraction peaks consistent with standard ZIF-67, indicating the successful synthesis of the three MOFs materials.
[0062] 2) Figure 2 The following are scanning electron microscope (SEM) images of the materials obtained in Examples 1 to 3. Figure 2 It can be seen that the three materials all present a regular dodecahedral morphology. The average size of the material in Example 1 is 300 nm, the average size of the material in Example 2 is 700 nm, and the average size of the material in Example 3 is 1.7 μm.
[0063] Test Case
[0064] Fragrance adsorption capacity test
[0065] 3-Acetylpyridine was selected as a representative heterocyclic fragrance.
[0066] 50 mg of the materials prepared in Example 1, Example 2, and Example 3 and 200 μL of 3-acetylpyridine were respectively placed in the same sealed container, and the container was placed in an oven at 80° C. for adsorption for 8 h.
[0067] 5 mg of the material adsorbing 3-acetylpyridine was dispersed in 2 mL of ethanol, extracted by ultrasonication at 40 ° C for 30 min, centrifuged, and the supernatant was filtered and placed in a headspace bottle for concentration testing using gas chromatography-mass spectrometry. The gas chromatography-mass spectrometry test conditions were as follows: the injection mode was splitless injection, and the injection volume was 1 μL; the temperature program was an initial temperature of 40 ° C, maintained for 3 min, and then increased to 260 ° C at a rate of 10 ° C / min and maintained for 10 min. Other parameters were injection volume: 1.0 L; carrier gas: helium (99.999%); ion source temperature: 230 ° C; transfer line temperature: 260 ° C; ionization energy: 70 eV; quadrupole temperature: 150 ° C; carrier gas flow rate: 1.0 mL / min; ionization mode: EI; electron multiplier voltage: 1635 V; solvent delay 9 minutes. The results were matched with the NIST11.L database to determine the 3-acetylpyridine fragrance content.
[0068] Figure 3 The BET test results of the MOFs materials in Examples 1 to 3 include N2 adsorption-desorption isotherms (a) and pore size distribution curves (b). Figure 3 It can be seen that the prepared MOFs materials all have high specific surface areas and rich pore structures. Among them, 300nm ZIF-67 has a large specific surface area and a large number of microporous structures.
[0069] Figure 4 is the adsorption performance of the materials in Examples 1 to 3 for 3-acetylpyridine. Figure 4It can be seen that ZIF-67-300 has the strongest adsorption capacity for 3-acetylpyridine, with an adsorption amount of 1083 mg / g; followed by ZIF-67-700, with an adsorption amount of 535 mg / g; the adsorption capacity of ZIF-67-1700 is relatively poor, at 239 mg / g.
[0070] Figure 5 is the retention rate of 3-acetylpyridine after the MOFs material in Examples 1 to 3 is placed at room temperature for 20 days after adsorption of 3-acetylpyridine. Figure 5 It can be seen that the retention rate of ZIF-67-300 is 62.2%, the retention rate of ZIF-67-700 is 48.7%, and the retention rate of ZIF-67-1700 is 97.0%.
[0071] 4) Flavor release performance test
[0072] The materials after the materials in Examples 1 to 3 adsorbed the fragrance were placed in an environment of 80°C, and the fragrance content in the materials was measured at regular intervals. The results are shown in Table 1. Figure 6 .
[0073] Figure 6 The following is a graph showing the aroma release curve of the materials in Examples 1 to 3 at 80°C over time. Figure 6 It can be seen that the material in Example 1 prolongs the release time of 3-acetylpyridine in an environment of 80° C. and has a strong sustained release ability. Moreover, the material in Example 1 only releases 6.3% within 60 minutes under a high temperature condition of 80° C.
[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a heterocyclic fragrance controlled-release MOFs material, comprising the following steps: Mixing soluble cobalt salt, 2-methylimidazole and solvent, and performing crystallization to obtain heterocyclic fragrance controlled slow-release MOFs material; The solvent is methanol or water; When the solvent is methanol: the usage ratio of the soluble cobalt salt, 2-methylimidazole and solvent is 2.0-3.0 g: 6.0-7.0 g: 400 mL; or, the usage ratio of the soluble cobalt salt, 2-methylimidazole and solvent is 3.0-4.0 g: 3.0-4.0 g: 200 mL; the crystallization temperature is 15-30° C.; When the solvent is water, the usage ratio of the soluble cobalt salt, 2-methylimidazole and water is 0.3-1.0 g:5.0-6.0 g:80-100 mL; and the crystallization temperature is 50-80° C.
2. The preparation method according to claim 1, characterized in that: The soluble cobalt salt is cobalt nitrate, cobalt chloride, cobalt acetate or cobalt sulfate.
3. The preparation method according to claim 2, characterized in that: The soluble cobalt salt, 2-methylimidazole and solvent are mixed for 1 to 10 minutes.
4. The preparation method according to claim 3, characterized in that: The crystallization time is 12 to 24 hours.
5. The heterocyclic fragrance controlled sustained-release MOFs material prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the heterocyclic flavor controlled-release MOFs material according to claim 5 as an adsorbent in the adsorption and controlled-release of flavors and fragrances.
7. The use according to claim 6, characterized in that: The method of application comprises the following steps: The heterocyclic fragrance controlled-release MOFs material and the heterocyclic fragrance are placed in the same closed environment for adsorption.
8. The use according to claim 7, characterized in that: The heterocyclic fragrance includes one of 3-acetylpyridine, 2-acetylpyridine, 2-acetylpyrrole and 2,3,5-trimethylpyrazine.
9. The use according to claim 8, characterized in that: The usage ratio of the heterocyclic fragrance controlled-release MOFs material to the heterocyclic fragrance is 30-60 mg:100-300 μL.
10. The use according to claim 9, characterized in that: The adsorption temperature is 50-100° C., and the adsorption time is 5-10 hours.